Childhood Trauma and Insomnia Increase Suicidal Ideation in Schizophrenia Patients: A Cross-Sectional Study - Zhang, Yaoyao; Fang, Xinyu; Tang, Bei; Fan, Kaili; Wen, Na; Zhao, Ke; Xu, Weiqian; Tang, Wei; Chen, Yi (Frontiers in Psychiatry, 2021)
Objectives: This study aimed to investigate the effect of childhood trauma, especially its specific dimensions, and clinical risk factors for suicidal ideation in patients with schizophrenia. Methods: A total of 83 inpatients with schizophrenia were enrolled and divided into two groups: with suicidal ideation (n = 33) and without suicidal ideation (n = 50). All participants were administered the Childhood Trauma Questionnaire-Short Form, the Insomnia Severity Index, the Beck Scale for Suicide Ideation, the Modified Overt Aggression Scales, the auditory hallucination rating scale, the Hamilton Rating Scale of Depression and the Positive and Negative Syndrome Scale. Results: In our sample, 39.8% of the subjects had suicidal ideation, and 60.6% of them had suffered from childhood trauma. Patients with suicidal ideation had a higher Insomnia Severity Index score, Physical neglect score, the Childhood Trauma Questionnaire-Short Form total score (all P < 0.05) compared to those without. The logistic regression analysis revealed that physical neglect in Childhood Trauma Questionnaire was significantly associated with suicidal ideation (OR = 5.46, P < 0.05, 95% CI = 0.007–0.483). Further stepwise multiple linear regression identified that insomnia (β = 0.272, P = 0.011) and physical neglect (β = 0.257, P = 0.017) were strong risk factors for the severity of suicidal ideation in patients with schizophrenia. Mediation analysis showed that insomnia played a complete mediating role between physical neglect and suicidal ideation. Conclusion: Our results indicate that childhood maltreatment of physical neglect is a strong independent risk factor for suicidal ideation in schizophrenia. The risk is probably aggravated by the poor quality of sleep. Early screening and psychosocial treatment are recommended for psychotic individuals with a trauma history.